HW4sol - -f (2) x-2 = lim x 2-f ( x )-f (2) x-2 m = 4 ....

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
M408C, Homework 4 — Solution Instructor: Guoliang Wu 1. Find f 000 ( x ) where f ( x ) = 3 x + 4 x 5 . Solution. Since f ( x ) = x 1 / 3 + x 5 / 4 , f 0 ( x ) = 1 3 x - 2 / 3 + 5 4 x 1 / 4 f 00 ( x ) = - 2 9 x - 5 / 3 + 5 16 x - 3 / 4 f 000 ( x ) = 10 27 x - 8 / 3 - 15 64 x - 7 / 4 . 2. Let f ( x ) = ( x 2 if x 2 mx + b if x > 2 . Find the values of m and b that make f differentiable everywhere. Solution. Since f is differentiable, it must be continuous at x = 2. Thus, lim x 2 + f ( x ) = lim x 2 - f ( x ) 2 m + b = 4 . Moreover, f is differentiable at x = 2, lim x 2 + f ( x )
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: -f (2) x-2 = lim x 2-f ( x )-f (2) x-2 m = 4 . Therefore, b =-4. 3. Dierentiate y = csc ( + cot ). Solution. Use the product rule, y =-csc cot ( + cot ) + csc (1-csc cot ) =- csc cot -csc cot 2 + csc -csc 2 cot 1...
View Full Document

This note was uploaded on 12/03/2010 for the course M 408c taught by Professor Mcadam during the Fall '06 term at University of Texas at Austin.

Ask a homework question - tutors are online